Two letters from Mr. Burke to gentlemen in the city of Bristol, on the bills depending in parliament relative to the trade of Ireland (printed for J. Dodsley, 1778)
Addressed to Samuel Span to Mess. ******* ****** and Co., Bristol. - Mess. ******* ****** and Co. are Harford, Cowles and Co.